Matka Boska Szkaplerzna w ikonografii - Wasilewska, Jolanta (Archiwa, Biblioteki i Muzea Kościelne, 2016)
One of the many representations of the Virgin Mary in the Carmelite art is Our Lady of the Scapular. It is a specific artistic image connected with the liturgy of the altar, which is also the centre around which the life of the brotherhood revolves. The cult of Our Lady of the Scapular, promoted by the Carmelites, is one of the oldest forms of Marian devotion. Over the centuries, it has achieved great popularity in all social circles. The images of Our Lady of the Scapular are represented in either Mary’s bust or her entire figure, sitting or standing, usually with the Child in her arms or on her lap, holding a sceptre in one hand, in the second a scapular or a scapular in both hands; sometimes Infant Jesus holds a scapular. Scapular images also alluded to the Immaculate Conception. If the attribute of the scapular was not painted originally, it was added later or two pieces of cloth were attached to the image (sculptures). When miraculous paintings were covered with a silver or gold dress, scapulars also appeared on a flap piece of metal. The accepted representations of Our Lady of the Scapular were used as ornaments for feretra and banners connected with brotherhoods’ celebrations. Similar images can be found in books, icons and sculptures devoted to the practice of the brotherhood of the scapular.